Rienhoff's jejunal anti-peristaltic loop: On the subject of an observation - Gilardoni, Federico; Laviña Risso, Raúl; Suárez Meléndez, José; Silva García, Ernesto (Cirugía del Uruguay, 1982)
An obsevation after esophageal-gstric esection for cancer followed by an antiperistaltic jejunal interpoition, is presented. The aniphyioloical nature of Rienhoff's procedure ws demonstrated by he evolution. Experimentation is conluive nd hows that the interpoition of portions of the small intestine in an antiperistaltic way; constitutes an obstacle to the nomal digestive ransit. In spite of Goñi-Moreno's point of view favoring the procedure and sone occaional succesful caes; Orsoni's reports and our own observation denote the dangerous nature of the procedure.